2014
DOI: 10.1097/grf.0000000000000070
|View full text |Cite
|
Sign up to set email alerts
|

The Contraceptive CHOICE Project Round Up

Abstract: The Contraceptive CHOICE Project was a prospective cohort study of 9,256 women in the St. Louis area. The project provided no-cost reversible contraception to participants for 2-3 years with the goal of increasing uptake of long-acting reversible contraception and decreasing unintended pregnancy in the area. This manuscript will provide a brief summation of the major findings to date including the dramatic effect the project had on unintended pregnancy and abortion rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
2
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(103 citation statements)
references
References 21 publications
1
91
2
9
Order By: Relevance
“…22,23 With the barriers of cost, knowledge, and access removed, 75 percent of participants chose a long-acting reversible contraception method. Participants who chose such methods had higher rates of continuing to use their device and of satisfaction at twelve and twenty-four months of follow-up.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…22,23 With the barriers of cost, knowledge, and access removed, 75 percent of participants chose a long-acting reversible contraception method. Participants who chose such methods had higher rates of continuing to use their device and of satisfaction at twelve and twenty-four months of follow-up.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Santelli et al, [4] found that improvements in contraceptive use accounted for 86% of the reduction in teen pregnancy between 1995 and 2002 for teens aged [15][16][17][18][19]. The authors also found that improved contraceptive use accounted for 77% of the reduction in pregnancies among teens aged 15-17.…”
Section: Introductionmentioning
confidence: 78%
“…First, policies and programs should continue to target sexually active youth who do not use contraception. Second, teen pregnancy rates could decline further if policymakers can increase the effectiveness of method use among existing contraceptors-for example, by providing evidence-based contraceptive counseling, affordable services and same-day prescriptions/insertions [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The continuation rates were 86 % in the LARC group versus 55 % who chose other temporary methods at the end of one year. Finally, women who used short-acting methods were 20 times more likely than women using an implant or IUD to have an unintended pregnancy at the end of one year which is most important in this age group [9]. It was found that pregnancy, birth, and abortion rates were low among teenage girls, and women enrolled in a project that removed financial and access barriers to contraception and informed them about the particular efficacy of LARC methods.…”
Section: Larc For Teensmentioning
confidence: 99%
“…Recent, large-scale research has shown how effective longacting contraception can be. Long-acting reversible contraceptive (LARC) methods have been shown to be acceptable to teens and young women, with higher continuation rates than shorter-acting methods [9]. In a study done in 10,000 adolescent girls, 75 % chose an implant or IUD when properly counselled.…”
Section: Larc For Teensmentioning
confidence: 99%